Existence of Coincidence Point In 𝐶∗-Algebra Valued Metric Space - Rishi Dhariwal; Deepak Kumar (Science & Technology Asia, 2025)
In the present manuscript, we established some results on coincidence points for two pairs of compatible and weakly compatible mappings satisfying a generalized contraction with a pair of partially weakly increasing mapping in ordered𝐶∗-algebra valued metric space. Moreover, integral type contractions in space provide a few implications for the main result. The result is an extension and generalization of several metric space results available.